Assessment of cerebral small vessel disease predicts individual stroke risk. Issue 12 (23rd August 2012) - Poels, Mariëlle M F; Steyerberg, Ewout W; Wieberdink, Renske G; Hofman, Albert; Koudstaal, Peter J; Ikram, M Arfan; Breteler, Monique M B
Abstract : Background: Despite several known risk factors it is still difficult to foresee who will develop a stroke and who will not. Vascular brain damage, visualised with MRI, reflects how the brain tolerates the effects of vascular risk factors and may therefore be relevant in predicting individual stroke risk. Objective: To examine whether the presence of small vessel disease on brain MRI could improve the prediction of stroke beyond the classic stroke risk factors from the 1991 Framingham Stroke Risk Function. Methods: 1007 community-dwelling elderly people, free of stroke at baseline were included in the study. Small vessel disease—that is, the presence of silent brain infarcts (SBI) and white matter lesions (WML), was scored on MRI scans obtained in 1995–6. 10-Year stroke risk prediction was assessed by the C statistic and by reclassification adding SBI and WML to a risk model including the classic stroke risk factors. Results: During 10-years of follow-up 99 strokes occurred. Individual stroke risk prediction significantly improved from 0.73 (95% CI 0.67 to 0.78) to 0.75 (0.69 to 0.80) in men and from 0.69 (0.64 to 0.75) to 0.77 (0.71 to 0.82) in women after inclusion of SBI and periventricular WML to the stroke risk factors. Reclassification occurred mainly in the intermediate stroke risk group (men 26%; women 61% reclassified). Conclusions: Assessment of small vessel disease with MRI beyond the classic stroke risk factors improved the prediction of subsequent stroke, especially in women with an intermediate stroke risk. These findings support the use of MRI as a possible tool for better identifying people at high risk of stroke.